Nonoperative management of rectal cancer - Williams, Hannah; Lee, Christina; Garcia-Aguilar, Julio (Frontiers in Oncology, 2024)
The management of locally advanced rectal cancer has changed drastically in the last few decades due to improved surgical techniques, development of multimodal treatment approaches and the introduction of a watch and wait (WW) strategy. For patients with a complete response to neoadjuvant treatment, WW offers an opportunity to avoid the morbidity associated with total mesorectal excision in favor of organ preservation. Despite growing interest in WW, prospective data on the safety and efficacy of nonoperative management are limited. Challenges remain in optimizing multimodal treatment regimens to maximize tumor regression and in improving the accuracy of patient selection for WW. This review summarizes the history of treatment for rectal cancer and the development of a WW strategy. It also provides an overview of clinical considerations for patients interested in nonoperative management, including restaging strategies, WW selection criteria, surveillance protocols and long-term oncologic outcomes.